2015
DOI: 10.1021/acs.jpcc.5b09940
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Exciton Self-Trapping in Pseudoisocyanine J-Aggregates Formed in Layered Polymer Films

Abstract: At low temperatures in the luminescence spectrum of pseudoisocyanine (PIC) J-aggregates formed in a layered polymer film an unusual broad red-shifted band appears. The analysis of spectral properties of PIC J-aggregates allowed us to ascribe the additional red band to the exciton self-trapped state. In a layered polymer film, PIC J-aggregates are found to possess a 2D island-like structure, which results in a barrier type of the exciton self-trapping with coexisting free and self-trapped excitons. Both the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 56 publications
(197 reference statements)
5
87
0
Order By: Relevance
“…This theoretical investigation is motivated by several studies that have noted deviations from Förster theory's characteristic − R 6 dependence on the rate of EET (the rate of EET is proportional to the square of the coupling) [41][42][43]. Any deviations from Förster theory could have an impact on design strategies for the development of mesoscopic energy harvesting materials [47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…This theoretical investigation is motivated by several studies that have noted deviations from Förster theory's characteristic − R 6 dependence on the rate of EET (the rate of EET is proportional to the square of the coupling) [41][42][43]. Any deviations from Förster theory could have an impact on design strategies for the development of mesoscopic energy harvesting materials [47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…[43] On the other hand, such disorder can also induce exciton self-trapping. [44] We note that both the almost linear PL intensity as a function of excitation fluence in lamellar films as well as the sub-linear behavior in platelets remained constant (in the error range for the exponent of ±0.05) within the temperature range of the measurements (Figure S9, Supporting Information). This suggests a temperature-independent charge generation and trapping rate and a minor role of temperature-driven exciton or charge diffusion for this kind of quenching process.…”
Section: Exciton Dynamics In Platelets and Lamellar Films At Low Tempmentioning
confidence: 77%
“…Based on the intensity increase by cooling, they claimed that the long-wavelength FL originates from the trapping states lying below the exciton states that are populated by the energy transfer from the excitons. Sorokin et al reported that PIC J-aggregates in layered films of poly­(sodium 4-styrenesulfonate) showed a broad FL band peaking at λ = 618 nm at T = 77 K. The authors assigned this FL to the emission from self-trapping exciton states, with the support of time-resolved FL spectroscopy measurements …”
Section: Resultsmentioning
confidence: 94%
“…Since the PIC J-aggregates embedded in polymer films are stable and resistant to photobleaching, these samples are well-suited for spectroscopic investigations. However, the optical properties of the J-aggregates in these samples differ considerably depending on the polymers used, as well as on the film fabrication methods, indicating that the interaction between the aggregates and the surrounding polymers strongly influences their optical properties. This may hinder the investigation of the intrinsic optical properties of J-aggregates. Moreover, the polymers that surround the J-aggregates prevent a direct measurement of their geometry, for example, using an atomic force microscope.…”
Section: Introductionmentioning
confidence: 99%